Preparation method and application of mineralized protein membrane
By using enzymatic mineralization method in GBR membrane to grow hydroxyapatite in protein membranes, forming a mineralized protein membrane with high mechanical properties and biocompatible, the insufficient mechanical properties and biocompatible existing GBR membranes are solved. The problem of bone regeneration promotion effect and environmental protection preparation have been achieved.
Patent Information
- Application Number
- CN202411135888.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-19
AI Technical Summary
The existing GBR membranes have shortcomings in mechanical properties and biocompatibility, and it is difficult to take into account high toughness and rigidity. The barrier capacity of the absorbable membranes has decreased affecting the therapeutic effect. New mineralized protein membranes need to be developed to promote bone regeneration.
The enzymatic mineralization method is used to grow hydroxyapatite mineralized in situ in the protein membrane to form a mineralized protein membrane composed of arthropod elastin and hydroxyapatite. The Gao Yang model is achieved through double-step chemical cross-linking and photoinitiator. Combination of quantity, fracture strength and flexibility.
It realizes excellent mechanical properties and biocompatibility of mineralized protein membranes, can effectively isolate soft tissue cells, promote the repair and regeneration of bone defect areas, and has a simple preparation process, low cost, and green and environmentally friendly.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomaterials, and in particular to a mineralized protein membrane and a preparation method and application thereof. Background Art
[0002] Guided bone regeneration (GBR) is a classic method for treating bone injury diseases. GBR membranes are required to prevent soft tissue from growing into bone defect areas. GBR membranes with excellent barrier effects are the key to the successful treatment of bone injury diseases. According to clinical needs, GBR membranes should first play the role of isolating cells and prevent the passage of soft tissue-related cells. In addition, the use of biofunctional GBR membranes can increase the rate of bone tissue regeneration, thereby shortening the treatment cycle. GBR membranes can be divided into two categories: non-absorbable and absorbable, both of which are widely used in clinical practice. Among them, non-absorbable GBR membranes can provide a better barrier for bone regeneration and do not have the problem of decreased mechanical properties, but they need to be removed by surgery later, which can easily cause secondary damage. On the contrary, absorbable GBR membranes are degradable, but their barrier capacity will gradually decrease and affect the treatment effect. Therefore, it is urgent to develop new GBR membranes to solve the problem of difficult balance between degradability and functionality.
[0003] Hydrogels, especially those based on biomacromolecules, are biodegradable and have adjustable mechanical properties, showing great potential in a variety of biomedical applications. However, in terms of mechanical properties, there is still a large gap between synthetic hydrogels and many natural hydrogels. For example, cartilage and skin can maintain high strength, stiffness and toughness at the same time under the condition of more than 50% water content. Although there have been many important breakthroughs in the field of synthetic hydrogels recently, especially double network hydrogels, which can even match the toughness of natural skin. However, the toughness of synthetic hydrogels often comes from high elongation, and the rigidity is still poor, making it difficult to provide effective support in applications. In the use scenario of GBR membranes, support can provide space for bone regeneration, which is conducive to increasing the rate of bone regeneration. In order to better meet the application requirements of GBR, the rigidity of hydrogel materials needs to be improved. Bionic mineralization is an effective way to improve the rigidity of materials, but mineralization is prone to cause brittleness of materials. In order to prepare hydrogel materials with both high toughness and rigidity, the in situ growth of amorphous minerals in the hydrogel matrix was achieved through the strategy of enzymatic mineralization, and a mineralized hydrogel material with both rigidity and toughness was obtained. At the same time, the inorganic minerals also gave the material biological activity. However, the biocompatibility problem of chemically synthesized materials limits further biomedical applications. Therefore, the development of enzymatic mineralization methods based on protein hydrogels is expected to achieve the preparation of new GBR membranes with excellent mechanical properties, biocompatibility and bioactivity. Summary of the invention
[0004] In view of this, the present invention provides a mineralized protein membrane and a preparation method and application thereof. The present invention provides a mineralized protein membrane for guiding bone regeneration and a preparation method thereof. The mineralized protein membrane in the present invention has excellent mechanical properties, can effectively isolate soft tissue cells, and has excellent biocompatibility and biological activity, and can effectively promote the repair and regeneration of bone defect sites.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The invention provides a mineralized protein membrane, comprising: a protein membrane and a mineral; the mineral comprises: a hydroxyapatite mineral.
[0007] In some embodiments of the present invention, in the above-mentioned mineralized protein membrane, the protein membrane comprises: elastin and functionalized or unfunctionalized polyethylene glycol.
[0008] In some embodiments of the present invention, in the mineralized protein film, the mass ratio of the elastin to the functionalized or unfunctionalized polyethylene glycol is 4:3.
[0009] In some embodiments of the present invention, in the above-mentioned mineralized protein film, the elastin has:
[0010] (1) the amino acid sequence shown in SEQ ID NO: 1; or
[0011] (2) An amino acid sequence obtained by replacing, deleting or adding one or more amino groups of the amino acid sequence shown in (1), and having the same or similar function as the amino acid sequence shown in (1); or
[0012] (3) An amino acid sequence that is at least 80% identical to the amino acid sequence shown in (1) or (2).
[0013] In some embodiments of the present invention, the sequence of SEQ ID NO: 1 is:.
[0014] In some embodiments of the present invention, the elastin in the mineralized protein film includes: arthropod elastic protein and positively charged elastin-like protein.
[0015] In some embodiments of the present invention, the arthropod elastic protein in the mineralized protein film has an amino acid sequence as shown in SEQ ID NO: 2: VGSGGRPSDSYGAPGGGNP.
[0016] In some embodiments of the present invention, the positively charged elastin-like protein in the mineralized protein film has an amino acid sequence as shown in SEQ ID NO: 3: VPGKGVPGKGVPGKGVPGKGVPGKG.
[0017] In some embodiments of the present invention, the functionalization in the mineralized protein membrane comprises: dialdehyde functionalization.
[0018] The present invention also provides a method for preparing the mineralized protein membrane. The mineralized protein membrane is obtained by in-situ mineralization of the mineralizer in the protein membrane.
[0019] In some embodiments of the present invention, the above preparation method comprises the following steps:
[0020] S1: mixing the elastin, the functionalized or unfunctionalized polyethylene glycol and alkaline phosphatase for first cross-linking;
[0021] S2: performing a second crosslinking on the product after the first crosslinking to obtain the protein film;
[0022] S3: mixing the protein film with a mineralized raw material to obtain the mineralized protein film.
[0023] In some embodiments of the present invention, in the above preparation method, the mineralized raw material includes: calcium glycerophosphate.
[0024] In some embodiments of the present invention, in the above preparation method, the mineralized raw material is added in the form of a solution; the concentration of the solution of the mineralized raw material is 11 g / L.
[0025] In some embodiments of the present invention, in the above preparation method, the solution of the mineralized raw material is obtained by mixing the mineralized raw material with a triethanolamine buffer solution.
[0026] In some embodiments of the present invention, the mixing time in the above preparation method S3 is 6 to 24 hours.
[0027] In some embodiments of the present invention, the mixing time in the above preparation method S3 is 6 hours, 12 hours or 24 hours.
[0028] In some embodiments of the present invention, in the above preparation method, the elastin is added in the form of a solution, and the final concentration of the elastin solution is 20-200 mg / mL.
[0029] In some embodiments of the present invention, the final concentration of the elastin solution in the above preparation method is 100 mg / mL.
[0030] In some embodiments of the present invention, the functionalized or unfunctionalized polyethylene glycol in the above preparation method is added in the form of a solution, and the final concentration of the functionalized or unfunctionalized polyethylene glycol solution is 50-300 mg / mL.
[0031] In some embodiments of the present invention, the final concentration of the functionalized or unfunctionalized polyethylene glycol solution in the above preparation method is 200 mg / mL.
[0032] In some embodiments of the present invention, in the above preparation method, the first crosslinking includes: imine bond crosslinking; the second crosslinking includes: photo crosslinking.
[0033] In some embodiments of the present invention, in the above preparation method, the temperature of the first cross-linking is 37° C. and the time is 2 hours.
[0034] In some embodiments of the present invention, the second cross-linking time in the above preparation method is 3 min, and the light intensity is 3.8 mW / cm 2 .
[0035] In some embodiments of the present invention, the photocrosslinking in the above preparation method includes the steps of adding a photoinitiator and an oxidant;
[0036] The photoinitiator includes terpyridine ruthenium; the oxidant includes persulfate ions.
[0037] In some embodiments of the present invention, the oxidant in the above preparation method includes: ammonium persulfate or potassium persulfate.
[0038] The present invention also provides the use of the mineralized protein membrane and / or the mineralized protein membrane obtained by the above preparation method in preparing bone repair products.
[0039] The present invention also provides a product, including: the mineralized protein membrane and / or the mineralized protein membrane obtained by the above preparation method.
[0040] The present invention provides a mineralized protein membrane for guiding bone regeneration, which is specifically composed of an arthropod elastin hydrogel mineralization template and a calcium phosphate mineral formed by in situ mineralization, wherein the protein hydrogel is obtained by two-step chemical cross-linking of arthropod elastin, and the amino acid sequence of arthropod elastin is MGQG[VGSGGRPSDSYGAPGGGNP(VPGKG)5VPG] 16WH6; The mineralized protein membrane can be used to promote the repair and regeneration of bone defect sites. The mineralized protein membrane product described in the present invention has excellent mechanical properties, including high Young's modulus, fracture strength and flexibility, and also has biocompatibility and bioactivity, can effectively isolate soft tissue cells, and can be used to promote the repair and regeneration of bone defect sites. In addition, the preparation process of the present invention is simple, does not require special equipment, is low in cost, and is green and environmentally friendly, which is conducive to the development and promotion of the next generation of tissue barrier membranes and bone repair materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below.
[0042] Figure 1 The SDS-PAGE gel electrophoresis diagram of the arthropod elastic protein prepared in Example 1 is shown;
[0043] Figure 2 The photos and scanning electron microscope images of the mineralized protein membranes prepared at different mineralization times in Examples 1, 2, and 3 are shown; wherein: a shows the change in the appearance of the protein hydrogel with the increase in mineralization time; b shows the change in the apparent mechanical properties of the mineralized hydrogel with the increase in mineralization time; c shows the scanning electron microscope image of the internal microstructure of the protein hydrogel with the increase in mineralization time;
[0044] Figure 3 The dark field scanning transmission electron microscope image of the mineralized protein membrane prepared in Example 3 after 24 hours of mineralization and the corresponding element distribution analysis image are shown;
[0045] Figure 4 The transmission electron microscope characterization and selected electron diffraction pattern of the ultrathin slice of the mineralized protein membrane prepared in Example 3 after 24 hours of mineralization are shown; wherein: a shows a transmission electron microscope image of the ultrathin slice sample of the mineralized protein hydrogel at a low magnification; b shows a transmission electron microscope image of the ultrathin slice sample of the mineralized protein hydrogel at a high magnification; c shows a high-resolution transmission electron microscope image of the ultrathin slice sample of the mineralized protein hydrogel and the corresponding lattice calibration; d shows a selected area electron diffraction pattern of the ultrathin slice sample of the mineralized protein hydrogel;
[0046] Figure 5 The mechanical properties of the mineralized protein membranes prepared at different mineralization times in Examples 1, 2, and 3 are shown; wherein: a is a comparison diagram of typical stress-strain curves of unmineralized and protein hydrogels at different mineralization times; b is a statistical diagram of the fracture strength of unmineralized and protein hydrogels at different mineralization times; c is a statistical diagram of the toughness of unmineralized and protein hydrogels at different mineralization times; d is a statistical diagram of the modulus of unmineralized and protein hydrogels at different mineralization times;
[0047] Figure 6The cell compatibility diagram of the mineralized protein membranes prepared at different mineralization times in Examples 2 and 3 is shown;
[0048] Figure 7 Figure 2 shows the mineralized protein membranes with different mineralization times prepared in Examples 2 and 3 guiding bone defect repair and regeneration. DETAILED DESCRIPTION
[0049] The invention discloses a mineralized protein membrane and a preparation method and application thereof.
[0050] It should be understood that the expression "one or more of..." includes each of the items recited after the expression individually and in various different combinations of two or more of the recited items, unless otherwise understood from the context and usage. The expression "and / or" in combination with three or more recited items should be understood to have the same meaning, unless otherwise understood from the context.
[0051] The use of the terms "comprising", "having" or "containing", including their grammatical synonyms, should generally be understood as open and non-restrictive, for example not excluding other unrecited elements or steps, unless otherwise specifically stated or otherwise understood from the context.
[0052] It should be understood that the order of steps or the order in which certain actions are performed is not important as long as the present invention remains operable. In addition, two or more steps or actions may be performed simultaneously.
[0053] The use of any and all examples or exemplary language, such as "for example" or "including", herein is intended only to better illustrate the invention and does not limit the scope of the invention unless otherwise claimed. No language in this specification should be construed as indicating that any non-claimed element is essential to the practice of the invention.
[0054] In addition, the numerical ranges and parameters used to define the present invention are approximate values, and the relevant values in the specific embodiments have been presented as accurately as possible. However, any numerical value inherently inevitably contains standard deviations due to individual test methods. Therefore, unless otherwise expressly stated, it should be understood that all ranges, quantities, values and percentages used in this disclosure are modified by "about". Here, "about" generally means that the actual value is within plus or minus 10%, 5%, 1% or 0.5% of a specific value or range.
[0055] The invention provides a mineralized protein membrane which can be used for guiding bone tissue repair and regeneration, comprising an arthropod elastin hydrogel mineralized template and hydroxyapatite mineralized products formed by in-situ mineralization; the mineralized protein membrane has excellent biocompatibility and bioactivity.
[0056] The mineralized protein membrane provided by the embodiment of the present invention exhibits excellent mechanical properties, including high Young's modulus, fracture strength and flexibility, can effectively isolate soft tissue cells, and exhibits good biocompatibility and biological activity. In addition, the mineralized protein membrane provided by the present invention can be used in biomedical applications to promote the repair and regeneration of bone defects.
[0057] The embodiment of the present invention uses the arthropod elastic protein hydrogel as a mineralization template, which is a new mineralization template on a macroscopic scale. Specifically, the mineralization template is a protein hydrogel network formed by cross-linking arthropod elastic protein with dialdehyde functionalized polyethylene glycol, and further cross-linking of the tyrosine of the protein by free radical reaction under visible light excitation. The macroscopic scale referred to in the embodiment of the present application refers to mineralization visible to the naked eye, compared to the nanoscale.
[0058] In an embodiment of the present invention, the mineralized protein membrane provided for promoting the repair and regeneration of bone defect sites is prepared by mineralizing an arthropod elastin hydrogel template; the mineralized template is a protein hydrogel obtained by secondary crosslinking of arthropod elastin with dialdehyde functionalized polyethylene glycol and visible light-excited tyrosine free radical reaction. That is, the mineralized template described in the embodiment of the present invention is composed of arthropod elastin hydrogel, the main components of which are arthropod elastin and dialdehyde functionalized polyethylene glycol.
[0059] The mineralized protein membrane described in the embodiment of the present invention is composed of arthropod elastic protein hydrogel and hydroxyapatite formed by in situ mineralization, that is, hydroxyapatite can be grown in situ inside the mineralized template. Hydroxyapatite, also known as hydroxyapatite, is the natural mineralization of calcium apatite (Ca5(PO4)3(OH)), often written as (Ca 10 (PO4)6(OH)2) form.
[0060] In an embodiment of the present invention, the mineralization process of the arthropod elastic protein hydrogel is carried out under the guidance of alkaline phosphatase (purchased from Sigma-Aldrich). Specifically, during the preparation of the protein hydrogel, alkaline phosphatase will be mixed with the arthropod elastic protein solution, and the dialdehyde functionalized polyethylene glycol can also react with the lysine residues of the alkaline phosphatase, so the alkaline phosphatase is covalently fixed in the protein hydrogel network. Alkaline phosphatase can hydrolyze the calcium glycerophosphate mineralization solution to produce free phosphate radicals and further form hydroxyapatite minerals with calcium ions in the solution, thereby completing the mineralization process of the protein hydrogel.
[0061] The arthropod elastic protein described in the present invention is a recombinant protein obtained by fusion expression of arthropod elastic protein obtained by a biosynthetic method and a positively charged elastic protein-like protein. The amino acid sequence of the arthropod elastic protein block is VGSGGRPSDSYGAPGGGNP, and the amino acid sequence of the positively charged elastic protein-like protein block is (VPGKG)5. The engineered Escherichia coli is used as a host cell, a plasmid is constructed according to the protein amino acid sequence, and then introduced into Escherichia coli for protein expression. The amino acid sequence of the chimeric protein is MGQG[VGSGGRPSDSYGAPGGGNP(VPGKG)5VPG] 16 WH6.
[0062] The present invention provides a method for preparing a mineralized protein film as described above, comprising the following steps:
[0063] S1. The recombinant protein of elastin fused with positively charged elastin-like protein is expressed and synthesized by Escherichia coli host cells, which is referred to as elastin for short.
[0064] S2. Dissolve the synthesized arthropod elastin and alkaline phosphatase in water, and mix with a dialdehyde functionalized polyethylene glycol aqueous solution to form imine bonds after standing, which is the first step of cross-linking of the protein hydrogel.
[0065] S3. Adding an aqueous solution of terpyridine ruthenium to the mixed solution, and irradiating the mixed solution with visible light in the presence of persulfate ions to achieve the second step of cross-linking of the protein hydrogel, and the mixed solution becomes a gel.
[0066] S4. The cross-linked protein hydrogel is placed overnight to fully cross-link and form a protein film. The protein film is then placed in a calcium glycerophosphate aqueous solution (triethanolamine is used as a buffer) to finally achieve mineralization of the protein film.
[0067] Preferably, the concentration of the arthropod elastic protein solution is 20-200 mg / mL.
[0068] Preferably, the concentration of the dialdehyde functionalized polyethylene glycol aqueous solution is 50-300 mg / mL.
[0069] Preferably, the mass ratio of the arthropod elastic protein to the dialdehyde functionalized polyethylene glycol is 1:2 to 2:1, and a more preferred ratio is 4:3.
[0070] Preferably, the amounts of alkaline phosphatase and ammonium persulfate are 0.1 mg and 0.5 mg respectively (corresponding to 20 mg of arthropod elastic protein).
[0071] Preferably, the first step cross-linking temperature is 37° C. and the cross-linking time is 2 h.
[0072] Preferably, the photocrosslinking time is 3 min (light intensity is about 3.8 mW / cm 2 ).
[0073] Preferably, the concentration of the triethanolamine aqueous solution is 0.2 M and the pH is 9.8.
[0074] Preferably, the concentration of the mineralization solution is 11 g / L (pure water accounts for 40% and triethylamine buffer accounts for 60%).
[0075] Preferably, the mineralization time of the protein film is 6 to 24 h.
[0076] In Examples 1 to 3 and the effect examples of the present invention, the raw materials and reagents used can be purchased from the market.
[0077] The present invention will be further described below in conjunction with embodiments:
[0078] Example 1
[0079] (1) Prokaryotic expression of elastic protein. The amino acid sequence of elastic protein recombinantly expressed in the present invention is MGQG[VGSGGRPSDSYGAPGGGNP(VPGKG)5VPG] 16WH6, firstly, the pET25b expression vector containing the arthropod elastic protein gene sequence was transformed into Escherichia coli BL21 (DE3) competent cells, and then further proliferated and expressed. Specifically, 3 μL of pET25b expression plasmid was added to the BL21 competent cells in an ice bath and incubated for 30 min to bring the plasmid and competent cells close. Subsequently, the expression vector was transferred to the BL21 competent cells by heat shock in a 42°C water bath for 90 s, and the ice bath was continued for 2 min to complete the plasmid transformation. 400 μL of sterile LB medium (peptone 10 g / L, yeast powder 5 g / L, sodium chloride 10 g / L) was added to the transformed BL21 competent cells and cultured for about 45 min, then solid medium was plated and cultured in a 37°C incubator overnight. Single colonies in the solid medium were selected and transferred to 20 mL of LB medium with a sterile pipette tip and cultured in a shaker for about 12 h (37°C, 220 rpm), then glycerol bacteria were prepared and frozen in a -20°C refrigerator for use. Next, the protein was expressed. First, the seed culture was prepared. 1 mL of frozen glycerol bacteria and 200 μL of ampicillin solution (100 mg / mL) were added to 200 mL of LB medium and cultured in a shaker for about 6 h until the OD value of the culture reached 2. The seed culture was added to a 4 L large shake flask for continued culture (37°C, 220 rpm). The large shake flask contained 1 L of sterile TB medium (12 g / L peptone, 24 g / L yeast powder, 2.32 g / L potassium dihydrogen phosphate, 12.54 g / L potassium dihydrogen phosphate, 4 mL / L glycerol) and 1 mL of ampicillin solution. After about 4 hours of culture, the OD of the culture was about 0.8. IPTG solution (1 M) was then used to induce protein expression, and the culture temperature was changed to 28.5°C. The protein expression process was completed after about 12 hours of overnight culture. Finally, the bacteria were collected by centrifuge (8000 rpm, 15 min) and frozen in a -80°C refrigerator.
[0080] (2) Purification of arthropod elastic protein. Ni chromatography column and ion exchange column were used for purification, and molecular sieve desalting column was used for desalting. First, the bacterial cells after protein expression were thawed and resuspended in lysis buffer (500 mM sodium chloride, 50 mM trisodium phosphate, 20 mM imidazole, pH 7.4), and the final bacterial solution concentration was 100 g / L. DNA enzyme and lysozyme were added and stirred for 1 h. Then, the bacteria were broken by high-pressure crusher, and Escherichia coli fragments were removed by centrifugation in a high-speed refrigerated centrifuge (14000 rpm, 30 min), and the supernatant was retained for further purification. First, the target protein was purified using a Ni affinity chromatography column connected to a purification instrument, in which the loading buffer was a mixed solution of 500 mM sodium chloride, 50 mM trisodium phosphate, and 20 mM imidazole at pH 7.4, and the elution buffer was a mixed solution of 500 mM sodium chloride, 50 mM trisodium phosphate, and 350 mM imidazole at pH 7.4. The target protein solution was initially purified by gradient elution, and then further dialyzed and purified by cation exchange column. The loading buffer in the ion exchange process was a mixed solution of 50 mM sodium chloride and 50 mM trisodium phosphate at pH 7.4, and the elution buffer was a mixed solution of 5 M sodium chloride and 50 mM trisodium phosphate at pH 7.4. The target protein solution was also obtained by gradient elution, and the excess salt in the protein solution was removed by a desalting column. Finally, the protein sample was obtained by freeze drying and stored in a -80°C refrigerator.
[0081] (3) Preparation of protein hydrogel. The elastin hydrogel was obtained by two-step crosslinking. First, dialdehyde-functionalized polyethylene glycol was used to react with the lysine residues in elastin to undergo a Schiff base reaction, and then the free radical reaction between the tyrosine residues in elastin was initiated by light. Specifically, 20 mg of elastin was prepared into a 100 mg / mL aqueous solution, and 15 mg of dialdehyde-functionalized polyethylene glycol was prepared into a 200 mg / mL aqueous solution. Then, the elastin and polyethylene glycol solutions were mixed evenly. In addition, the mixed solution also contained 0.1 mg of alkaline phosphatase (ALP) and 0.5 mg of ammonium persulfate. The mixed solution was placed in a 30°C oven for 2 h. At this point, the initial pre-crosslinking of the protein and dialdehyde-functionalized polyethylene glycol was completed, and the solution viscosity increased compared to the initial state. Then, 5 μL of terpyridine ruthenium (5 mg / mL) aqueous solution was added to the pre-crosslinking solution, mixed evenly, and poured into a polytetrafluoroethylene mold. Finally, photocrosslinking was performed using a white light flashlight (light intensity of 0.5 mW / cm 2 ), irradiate for 3 min according to the cross-linking degree of the sample, form protein hydrogel after illumination, and place in the dark overnight to complete the final cross-linking reaction.
[0082] (4) Enzymatic mineralization of protein hydrogel. The mineralization of arthropod elastic protein hydrogel is carried out under the induction of alkaline phosphatase. The mineralization buffer solution used in the present invention is a triethanolamine aqueous solution (0.2 M, pH 9.8), which is used to stabilize the pH of the mineralization solution. Next, 11 g of calcium glycerophosphate is dissolved in 400 mL of pure water and 600 mL of mineralization buffer. After sufficient stirring and dissolution, the insoluble matter in the mineralization solution is removed through a 0.4 μm filter membrane to complete the preparation of the mineralization solution. The pre-prepared arthropod elastic protein hydrogel is directly placed in the prepared mineralization solution for mineralization. 50 mL of mineralization solution is used for 30 mg of hydrogel sample, and the mineralization time is 6 h.
[0083] Example 2
[0084] All methods were the same as those in Example 1, except that the mineralization time of the protein hydrogel was changed to 12 h.
[0085] Evaluation experiment of the effect of mineralized protein membrane on bone regeneration. In order to evaluate the barrier effect of mineralized protein hydrogel in vivo, we used a rat skull defect model to compare the healing speed of animals treated with different barrier materials, including a blank control group, a protein hydrogel group, and a mineralized protein hydrogel group. Specifically, 6-week-old male SD rats were used for the experiment, and two 5 mm diameter defect models were made in the skull area of each rat using a skull drill. All barrier materials were cut into a size of approximately 7 mm in diameter and covered on the skull defect site. Finally, all rats were sutured and kept for observation.
[0086] Example 3
[0087] All methods were the same as those in Example 1, except that the mineralization time of the protein hydrogel was changed to 24 h.
[0088] Effect example
[0089] Figure 1 Sodium dodecyl sulfate-polyacrylamide (SDS-PAGE) gel electrophoresis analysis of the arthropod elastic protein prepared in Example 1 of the present invention ( Figure 1 a) and matrix-assisted laser desorption ionization time-of-flight mass spectrometry ( Figure 1 b) Results. In the gel electrophoresis, a single band appeared between the 70-100 kDa protein standard and no obvious impurity protein bands appeared, indicating that the target protein with high purity was obtained after purification ( Figure 1 a). Mass spectrometry results showed that the molecular weight of biosynthesized arthropod elastic protein was about 67 kDa.
[0090] Figure 2 The photos of the mineralized protein membranes prepared at different mineralization times in Examples 1, 2, and 3 of the present invention are shown in FIG. Figure 2a and b) and scanning electron microscopy images ( Figure 2 c). The unmineralized protein hydrogel is transparent and has flexible mechanical properties in the film state. After the hydrogel is naturally dried, it has a very flat and smooth microscopic surface morphology. After 6 hours of mineralization, the protein hydrogel changes from the initial transparent state to white opaque, indicating that inorganic minerals are rapidly formed inside the protein hydrogel under the induction of alkaline phosphatase. With the increase of mineralization time, the appearance of the protein hydrogel does not change further significantly ( Figure 2 a). The stiffness of the protein hydrogel before and after mineralization also changed significantly. The protein hydrogel film before mineralization was very soft and had no self-support. As the mineralization time increased, the stiffness of the protein hydrogel gradually increased, and it showed self-support after 12 h of mineralization. When the mineralization time increased to 24 h, the stiffness of the protein hydrogel continued to increase, but it still maintained excellent flexibility and could be bent arbitrarily without any damage to the appearance of the material ( Figure 2 b). We also used scanning electron microscopy to characterize the changes in the microscopic morphology of the protein hydrogel during mineralization. Figure 2 As shown in Figure c, after 6 h of mineralization, obvious mineral accumulation appeared inside the protein hydrogel, and after 12 h of mineralization, inorganic matter gradually grew, but there were still a large number of holes in the discontinuous mineralization state. When the mineralization time continued to increase to 24 h, a continuous mineralization structure gradually formed in the protein hydrogel, and no large-sized inorganic matter appeared ( Figure 2 c).
[0091] Figure 3 The dark field scanning transmission electron microscope image and the corresponding element distribution analysis image of the mineralized protein membrane prepared in Example 3 after 24 hours of mineralization. First, the protein hydrogel after mineralization for 24 hours and drying was embedded in resin and processed by ultrathin sectioning, and then the element distribution analysis of the ultrathin section samples was performed by transmission electron microscopy combined with X-ray spectrometer. Figure 3 As shown, in the sample area with obvious mineralization formation, Ca and P elements have a very high proportion, and the contours of the two elements are basically consistent with the mineralized area, which indicates that the inorganic matter formed by in situ mineralization is mainly calcium phosphate.
[0092] Figure 4 The transmission electron microscopy characterization and selected electron diffraction patterns of the ultrathin slices of the mineralized protein membrane prepared in Example 3 after 24 hours of mineralization. From the transmission electron microscopy images at different magnifications, it can be seen that the inorganic mineralization exists in the form of small-sized flakes and has a very high packing density and a certain short-range order ( Figure 4 a). The inorganic mineral units that make up the mineralized hydrogel are approximately 20 nm long and have a large aspect ratio ( Figure 4b). The formation of small-sized inorganic substances during the mineralization process is due to the presence of triethanolamine in the mineralization solution, which can form complexes with mineralization precursors, thereby effectively controlling the growth process of minerals. On the other hand, the double cross-linked network of protein hydrogel may have a certain confinement effect on minerals, preventing the fusion growth between minerals. The presence of lattice fringes can be vaguely seen through high-resolution transmission electron microscopy, which indicates that the calcium phosphate formed by in situ mineralization has certain crystal characteristics, but the crystallinity is poor ( Figure 4 c). In addition, two obvious diffraction rings can be seen in the selected area electron diffraction pattern of the mineralized protein hydrogel ultrathin section sample. Combined with the lattice size measurement of high-resolution transmission electron microscopy, it can be determined that the inorganic mineralization formed is hydroxyapatite with poor crystallinity ( Figure 4 d). The study of the microstructure of mineralized protein hydrogels also further explains why protein hydrogels can maintain good flexibility at high mineral content.
[0093] Figure 5 The mechanical properties of the mineralized protein membranes prepared at different mineralization times in Examples 1, 2, and 3 are shown in Figure 2. The typical stress-strain curves of the unmineralized protein hydrogel and the protein hydrogels at different mineralization times are shown in Figure 3. Figure 5 As shown in a. By comparison, it can be found that with the increase of mineralization time, the mechanical strength of the protein hydrogel gradually increases, and the corresponding elongation at break gradually decreases, but the protein hydrogel with a high degree of mineralization can still maintain an elongation at break of more than 15%. Subsequently, we statistically calculated the mechanical strength of the protein hydrogel (based on three sets of parallel mechanical test results). Specifically, the fracture strength of the unmineralized protein hydrogel is 154.2±2.6 kPa, and the toughness is 84.0 kJ / m 3 , the modulus is only about 0.35 MPa ( Figure 5 bd). Hydrogel materials usually exhibit very soft mechanical properties due to their high water content, so their modulus is generally low and it is difficult to provide strong support. As the in situ mineralization of protein hydrogels proceeds, inorganic matter is filled in the matrix in large quantities, gradually increasing its mechanical properties. After 6 h of mineralization, the fracture strength of the hydrogel was 671.0±33.6 kPa, the modulus increased to 2.0±0.3 MPa, and the toughness was also slightly improved, about 121 kJ / m 3 ( Figure 5 bd). By comparison, it can be found that a short period of mineralization can increase the modulus of the protein hydrogel by more than 5 times. As the mineralization continues, the mechanical strength of the protein hydrogel is further improved. After 12 h and 24 h of mineralization, the fracture strength increases to 1.8±0.3 MPa and 3.2±0.2 MPa, respectively. The fracture strength of the highly mineralized protein hydrogel is better than that of most of the hydrogel materials reported so far ( Figure 5b). More importantly, after 12 h and 24 h of mineralization, the modulus of the protein hydrogel increased to 43.5±8.3 MPa and 145.3±44.5 MPa, respectively, which is a high modulus property that is difficult to achieve with traditional synthetic polymer hydrogel materials ( Figure 5 d). At the same time, the toughness of the protein hydrogel gradually increased with the increase of mineralization time. The toughness of the protein hydrogel increased to about 367 kJ / m after 12 h and 24 h of mineralization, respectively. 3 and 457 kJ / m 3 ( Figure 5 c).
[0094] Figure 6 The cell compatibility diagram of the mineralized protein membranes prepared at different mineralization times in Examples 2 and 3. In order to evaluate the cell compatibility of the material, we used the live / dead cell staining assay to test the effects of mineralized 12 h protein membrane and mineralized 24 h protein membrane on cell viability and proliferation. Fluorescence microscopy showed that no dead cells were observed in the mineralized hydrogel group, and there was no significant difference compared with the blank control group and the polytetrafluoroethylene membrane group, indicating that these mineralized hydrogels have good cell compatibility. The specific experimental steps are as follows: L929 fibroblasts were incubated with polytetrafluoroethylene membrane, unmineralized protein membrane, mineralized 12 h protein membrane and mineralized 24 h protein membrane extract at 37 ° C and 5% CO2 for 24 hours. After incubation, 1 µL of Calcein-AM dye (1 mg / mL aqueous solution) and 1 µL of PI dye (1 mg / mL DMSO solution) were added to the cell culture medium, which was then incubated at 37°C for 15 min. The supernatant was replaced with fresh DMEM and imaged using a confocal microscope at excitation wavelengths of 488 nm and 561 nm.
[0095] Figure 7Figure 2 shows the bone defect repair and regeneration guided by mineralized protein membranes with different mineralization times prepared in Examples 2 and 3. In order to verify the osteogenesis of mineralized hydrogels in vivo, we used a rat skull critical bone defect model. Specifically, male SD rats weighing 200-250 grams (6-7 weeks old) were selected for in vivo studies. To construct a critical bone defect model in the skull cap, we exposed the rat skull and used a stainless steel skull drill to construct a bilateral full-thickness circular defect (5 mm in diameter). Subsequently, polytetrafluoroethylene membranes, collagen membranes, unmineralized protein membranes, mineralized 12 h protein membranes, and mineralized 24 h protein membranes were implanted into the bone defect area, respectively, while the blank control group was not implanted with any material after the defect was made. The skin incision was closed with 4-0 sutures. Twelve weeks after surgery, the rats were killed, their skulls were dissected, and fixed in 4% paraformaldehyde solution for 48 hours. In order to evaluate the in vivo osteogenesis of each group in depth, we used micro-computed tomography (micro-CT) to compare and analyze the osteogenesis area. The analysis results showed that the mineralized 12 h protein membrane had the largest area of new bone, followed by the mineralized 24 h protein membrane and collagen membrane. The unmineralized protein membrane also showed a certain osteogenesis effect, while the polytetrafluoroethylene membrane and blank control group had the least amount of new bone. The comparison showed that the mineralized 12 h protein membrane had an excellent effect on promoting osteogenesis, and the effect was better than the polytetrafluoroethylene membrane and collagen membrane products currently on the market.
[0096] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A mineralized protein film, characterized in that include: protein membranes and mineralization; The mineralized substances include hydroxyapatite mineralized substances.
2. The mineralized protein film according to claim 1, characterized in that The protein film comprises elastin and functionalized or unfunctionalized polyethylene glycol.
3. The mineralized protein film according to claim 1 or 2, characterized in that The elastin has: (1) the amino acid sequence shown in SEQ ID NO: 1; or (2) An amino acid sequence obtained by replacing, deleting or adding one or more amino groups of the amino acid sequence shown in (1), and having the same or similar function as the amino acid sequence shown in (1); or (3) An amino acid sequence that is at least 80% identical to the amino acid sequence shown in (1) or (2).
4. The mineralized protein film according to any one of claims 1 to 3, characterized in that The functionalization includes: dialdehyde functionalization.
5. The method for preparing a mineralized protein film according to any one of claims 1 to 4, characterized in that: The mineralized protein membrane is obtained by in situ mineralization of the mineralizer in the protein membrane.
6. The preparation method according to claim 5, characterized in that: The steps include: S1: mixing the elastin, the functionalized or unfunctionalized polyethylene glycol and alkaline phosphatase for first cross-linking; S2: performing a second crosslinking on the product after the first crosslinking to obtain the protein film; S3: mixing the protein film with a mineralized raw material to obtain the mineralized protein film.
7. The preparation method according to claim 6, characterized in that: The mineralized raw materials include: calcium glycerophosphate.
8. The preparation method according to claim 6 or 7, characterized in that: The mixing time in S3 is 6 to 24 hours.
9. Use of the mineralized protein membrane according to any one of claims 1 to 4 and / or the mineralized protein membrane obtained by the preparation method according to any one of claims 5 to 8 in the preparation of products for bone repair.
10. A product, characterized in that include: The mineralized protein film according to any one of claims 1 to 4 and / or the mineralized protein film obtained by the preparation method according to any one of claims 5 to 8.
Citation Information
Patent Citations
Resilin-like adhesive conductive hydrogel and preparation and application method thereof
CN109957117A
Cross-linked elastomeric proteins in polar nonaqueous solvents and uses thereof
CN112399861A
Recombinant protein hydrogel culture scaffold and preparation method thereof
CN114480269A
Recombinant collagen-chitosan-PEG-hydroxyapatite bone repair scaffold material as well as preparation method and application thereof
CN116099048A
Crosslinked elastomeric proteins in polar non-aqueous solvents and uses thereof
CN116239673A
